Prokaryotic and tissue-specific expression of RglKAT gene from Rehmannia glutinosa - ZHOU, Y Q; ZHANG, Y H; WANG, W S; WANG, X N; DUAN, H Y (The Indian Journal of Agricultural Sciences, 2015)
A 1640-bp full-length cDNA of the 3-ketoacyl-CoA thiolase gene was cloned from Rehmannia glutinosa L. leaf using RT-PCR and RACE. Bioinformatics analyses indicated that it contained one 1395-bp open reading frameencoding a thiolase of 464 amino acids with the predicted molecular weight of 49 kDa, and had a similarity of 73-82% to other species at the nucleotide level and 63-88% to other species at the amino acid level, respectively. The recombinant RglKAT was expressed in a bacterial system in an active form, analyzed by PAGE-CBB staining and purified using Ni-agarose chromatography. Real Time quantitative PCR analysis showed that relative expression levels of the RglKAT gene differed between R.glutinosa tissues, with the highest levels in the petals and the lowest in the early senescing stems. These results revealed that RglKAT gene could be cloned and heterogeneously expressed, and related to R. glutinosa growth and development.